Ribosomal DNA spacer-length polymorphisms in barley: mendelian inheritance, chromosomal location, and population dynamics. - Saghai-Maroof, M A (1984)
Spacer-length (sl) variation in ribosomal RNA gene clusters (rDNA) was surveyed in 502 individual barley plants, including samples from 50 accessions of cultivated barley, 25 accessions of its wild ancestor, and five generations of composite cross II (CCII), an experimental population of barley. In total, 17 rDNA sl phenotypes, made up of 15 different rDNA sl variants, were observed. The 15 rDNA sl variants comprise a complete ladder in which each variant differs in length from adjacent variants by approximately equal to 115 nucleotide pairs. Studies of four rDNA sl variants in an F2 population showed that these variants are located at two unlinked loci, Rrn1 and Rrn2, each with two codominant alleles. Using wheat-barley addition lines, we determined that Rrn1 and Rrn2 are located on chromosomes 6 and 7, respectively. The nonrandom distribution of sl variants between loci suggests that genetic exchange occurs much less frequently between than within the two loci, which demonstrates that Rrn1 and Rrn2 are useful as new genetic markers. Frequencies of rDNA sl phenotypes and variants were monitored over 54 generations in CCII. A phenotype that was originally infrequent in CCII ultimately became predominant, whereas the originally most frequent phenotype decreased drastically in frequency, and all other phenotypes originally present disappeared from the population. We conclude that the sl variants and/or associated loci are under selection in CCII.